Supporting and encouraging cycling in sustainable urban mobility planning. - Küster, Fabian (My University, 2019)
This document provides guidance on a specific topic related to Sustainable Urban Mobility Planning (SUMP). The core goal of Sustainable Urban Mobility Planning is to improve accessibility and quality of life by achieving a shift towards sustainable mobility. With 8 % of the EU population stating in a 2014 Eurobarometer survey that they use the bicycle as their primary mode of transportation. In order to unlock its full potential, cycling must be made as easy and as safe as possible. With the right support and framework, it should be feasible to increase cycle use across the EU by at least 50 % in the following years (ECF, 2017). The document shows how cycling can be supported on a local level.
Keywords: Fahrradverkehr; Nachhaltige Mobilität; Radwegenetz; Infrastrukturausbau; Mobilitätsverhalten; Fahrradverkehrinfrastruktur